Operational Safety: Development of Electronic System for Dynamic Balance Evaluation of Farm Tractors - De Souza Luciano, Matheus Daniel [UNESP]; Guarnetti Dos Santos, Joao Eduardo [UNESP]; Andreoli, Andre Luiz [UNESP]; Cagnon, Jose Angelo [UNESP]; Dos Santos Filho, Abilio Garcia [UNESP]; Arezes, P.; Baptista, J. S.; Barroso, M. P.; Carneiro, P.; Costa, N.; Melo, R.; Miguel, A. S.; et al. (Portuguese Soc Occupational Safety & Hygiene, 2013)
New farm tractors are acquired in order to look after its operators, offering higher comfort and safety. Due to the agricultural development in Brazil, new farm entrepreneurs are in search of new technologies in order to attend the productive demand. To improve the mechanical fleet prior in performance, comfort and safety of agricultural equipments and machinery, joined with appreciation of human capital, for improvement of human-machine relation. High-tech farm tractors are responsible for this change once that they are engaged in production enhance while adopt new electronic systems such as GPS (Global Positioning System) and several other embedded sensors (Anfavea 2010). The present study aimed at the development and evaluation of an inclinometer as a safety sensor device for farm tractors. Inasmuch as the high occurrences of accidents related with side bending of farm tractors. Also, there are not low cost equipments to warn the operator of the imminence of tipping of the farm tractor out of it dynamic balance.
Keywords: Inclinometer; operational safety; development of electronic system